Some helminth parasites of Larus pipixcan Wagler, Franklin's Gull - Taboada P., Dora A. (1974)
Between April and August 1973, Franklin’s Gull, Larus pipixcan Wagler, were captured in the Hacienda Cajamarquilla, 18 Km near Vitarte, Lima. We found acanthocephalans of genus Falsifilicollis and trematodes of genus Mesoophorodiplostomum.